Bioinformatics analysis of molecular mechanism of the expansion of hematopoietic stem cell transduced by HOXB4/HOXC4. Issue 8 (13th September 2016) - Xin, Chunlei; Zhao, Chunting; Yin, Xiangcong; Wu, Shaoling; Su, Zhan
Abstract : Objectives : We aimed to identify the potential HOXB4/HOXC4 downstream effectors and elucidate their regulatory mechanism in the expansion of hematopoietic stem cell (HSC). Methods : The microarray data GSE24379 were downloaded from Gene Expression Omnibus database, including 12 human CD34 + hematopoietic cells with irradiated EGFP-, HOXB4-, or HOXC4-transduced MS-5 cells, respectively. Then common differentially expressed genes (DEGs) in HOXB4- and HOXC4-treated hematopoietic cells (HOXB4&HOXC4.DEGs) were screened out. Protein–protein interaction (PPI) network was constructed and functional modules analysis was performed. Pathway enrichment analysis was performed using the Database for Annotation Visualization and Integrated Discovery. Besides, transcription regulatory network (TRN) was constructed to screen transcription factors (TFs) corresponding to HOXB4&HOXC4.DEGs. Results : A total of 408 HOXB4&HOXC4.DEGs (373 up- and 35 down-regulated) in hematopoietic cells were identified. Tumor protein p53 (TP53) had the highest degrees in PPI network. Cyclin B1 (CCNB1) was a hub node in Cluster 1. V-myc avian myelocytomatosis viral oncogene homolog (MYC) and MYC-associated factor X (MAX) were important TFs with higher degrees. Meanwhile, MYC, TP53, and CCNB1 were significantly enriched in cell cycle. Conclusion : MYC, MAX, TP53, and CCNB1 may be crucial HOXB4/HOXC4 downstream molecules potentially involved in HSCs expansion, and HOXB4 and HOXC4 homeoprotein could display positive effects on expansion of human HSCs via regulating these genes.